IMPORTANCE OF CONTRACT IN BUSINESS SERVICE - Bayjanova Ramuza Teńelbay qızı (International Multidisciplinary Journal for Research & Development, 2024)
Important aspects of the agreement in the development of entrepreneurship in scientific activities are considered. The system of civil contracts systematizes the problems of legal regulation of relations related to the definition of a contract and the implementation of scientific activities.